Inventarisasi Dan Kajian Etnobotani Tanaman Akuatik Di Taman Akuatik Kebun Raya Eka Karya Bali - A’tourrohman, Muhammad (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
Eka Karya Botanic Garden is an ex situ conservation area located in Bali's Biosphere Reserve. As part of the biosphere reserve, the Eka Karya Botanical Garden plays an important role in conservation, research, tourism and education programs. The purpose of this study is to inventory the types of aquatic plants found in the Aquatic Park of the Eka Karya Bali Botanic Garden and to reveal ethnobotanical aspects of the aquatic plants. This study uses an exploration method, with Aquatic Park as a location for sampling and observation. The results of the study showed that 12 aquatic plants were found, namely Nasturtium officinale, Cyperus flabelliformis, C. papyrus, Acorus calamus, Pontederia cordata, Echinodorus paleafolius, Eichhornia crassipes, Nymphaea pubescens, Nymphoides indica, Zantedeschia aethiopica, Hydrilla verticillata, and Pistia stratiotes. Besides being used as food, phytoremediation, handicraft, and ornamental plants, aquatic plants are also useful as herbal medicines such as anti-inflammatory drugs, mouth ulcers, diaphoretics, diuretics, flu, stomach ache, fever, headaches, dysentery, antimicrobials, antioxidants, and so forth. The processing method is by grinding, boiling, chewing, drying, and eaten directly